Antibiotic-resistant Campylobacter: an increasing problem. Issue 988 (5th March 2008) - Kent, A J; Farouk, L; Main, J; Hoare, J M
Abstract : The case is described of a 27-year-old woman who presented with an acute diarrhoeal illness. She was initially poorly responsive to antibiotics and developed lymphocytic ascites. Diagnosis was difficult to establish, and peritoneal tuberculosis was considered to be the most likely cause of her symptoms. Serological tests eventually confirmed Campylobacter jejuni infection. Campylobacter is one of the most common bacterial diarrhoeal infections, and complications, except for colitis, are rare except in specific disease states—for example, patients with cirrhosis or undergoing peritoneal dialysis. Antibiotic resistance is an increasing problem, and this may potentially lead to a greater incidence of complications in the future.